Diverging receptive and expressive word processing mechanisms in a deep dyslexic reader. (29th January 2016) - Ablinger, Irene; Radach, Ralph
Abstract: We report on KJ, a patient with acquired dyslexia due to cerebral artery infarction. He represents an unusually clear case of an "output" deep dyslexic reader, with a distinct pattern of pure semantic reading. According to current neuropsychological models of reading, the severity of this condition is directly related to the degree of impairment in semantic and phonological representations and the resulting imbalance in the interaction between the two word processing pathways. The present work sought to examine whether an innovative eye movement supported intervention combining lexical and segmental therapy would strengthen phonological processing and lead to an attenuation of the extreme semantic over-involvement in KJ's word identification process. Reading performance was assessed before (T1) between (T2) and after (T3) therapy using both analyses of linguistic errors and word viewing patterns. Therapy resulted in improved reading aloud accuracy along with a change in error distribution that suggested a return to more sequential reading. Interestingly, this was in contrast to the dynamics of moment-to-moment word processing, as eye movement analyses still suggested a predominantly holistic strategy, even at T3. So, in addition to documenting the success of the therapeutic intervention, our results call for a theoretically important conclusion: Real-time letter and word recognition routines should be considered separately from properties of the verbal output. Combining both perspectives may provide a promising strategy for future assessment and therapy evaluation. Highlights: We describe a novel therapy approach with "output" deep dyslexia. Innovative eye tracking methodology revealed moment-to-moment processing. Eye movement supported therapy combined segmental and lexical training. Therapy reduced semantic over-involvement and reactivated sublexical reading. Substantial discrepancies emerged between real-time word processing and verbal output.